Bis(mu-2-methyl-8-oxidoquinolin-1-ium-kappa O-2:O)bis[(acetato-kappa O-2,O `)(2-methyl-8-oxidoquinolin-1-ium-kappa O)bis(nitrato-kappa O-2,O `)lanthanum(III)] - Fazaeli, Y.; Amini, M.M.; Ng, S.W. (International Union of Crystallography, 2010)
The N-heterocycles in the centrosymmetric title compound, [La-2(C10H9NO)(4)(CH3COO)(2)(NO3)(4)], exist in the zwitterionic form. One heterocycle binds to a metal center whereas the other bridges two metal centers. Each La atom is chelated by an acetate and two nitrate groups and is surrounded by nine O atoms in a distorted tricapped trigonal-prismatic coordination environment. The N-H groups form intramolecular N-H center dot center dot center dot O hydrogen bonds. One of the nitrate ions is disordered over two positions in a 0.80 (3):0.20 (3) occupancy ratio.